Counteraction of Tetherin Antiviral Activity by Two Closely Related SIVs Differing by the Presence of a Vpu Gene - Nikovics, Kristina; Dazza, Marie-Christine; Ekwalanga, Michel; Mammano, Fabrizio; Clavel, François; Saragosti, Sentob (PLOS ONE, 2012)
In different primate lentiviruses, three proteins (Vpu, Env and Nef) have been shown to have anti-tetherin activities. SIVden is a primate lentivirus harbored by a Cercopithecus denti (C. denti) whose genome code for a Vpu gene. We have compared the activity of HIV-1 Vpu and of SIVden Vpu on tetherin proteins from humans, from C. denti and from Cercopithecus neglectus (C. neglectus), a monkey species that is naturally infected by SIVdeb, a virus closely related to SIVden but which does not encode a Vpu protein. Here, we demonstrate that SIVden Vpu, is active against C. denti tetherin, but not against human tetherin. Interestingly, C. neglectus tetherin was more sensitive to SIVden Vpu than to HIV-1 Vpu. We also identify residues in the tetherin transmembrane domains that are responsible for the species-specific Vpu effect. Simultaneous mutation (P40L and T45I) of human tetherin conferred sensitivity to SIVden Vpu, while abolishing its sensitivity to HIV-1 Vpu. We next analyzed the anti-tetherin activity of the Nef proteins from HIV-1, SIVden and SIVdeb. All three Nef proteins were unable to rescue virus release in the presence of human or C. denti tetherin. Conversely, SIVdeb Nef enhanced virus release in the presence of C. neglectus tetherin, suggesting that SIVdeb relies on Nef in its natural host. Finally, while HIV-1 Vpu not only removed human tetherin from the cell surface but also directed it for degradation, SIVden Vpu only induced the redistribution of both C. denti and C. neglectus tetherins, resulting in a predominantly perinuclear localization.